Photo-electrochemical water splitting behavior of CdSeQDs sensitized ferroelectric BaTiO3 perovskite heterostructure. (2021) - Soumya Rani, D.; Meera, M.R.
Abstract: We report the photo-electrochemical water splitting of CdSe quantum dots (QDs) sensitized BaTiO3 perovskite in a sacrificial electrolyte. The CdSe QDs are synthesized via hot injection method and perovskite BaTiO3 is synthesised via hydrothermal synthesis procedure. The CdSe QDs are sensitized to BaTiO3 using mercaptopropionic acid as linker to form heterostructure. The phase purity and crystallinity of CdSe QDs and BaTiO3 are examined using X-ray diffraction analysis and the morphologies are studied using transition electron microscopy (TEM) technique. The optical properties are examined using UV–Vis spectroscopy and the band gap of QDs and perovskite are derived. The XRD analysis of CdSe QDs reveals the high crystallinity with a cubic phase and tetragonal phase for BaTiO3 . The surface morphological observations demonstrate that BaTiO3 size in the range of 100–120 nm in size. The TEM analysis reveals single crystalline nature for the PbTiO3 nanoparticles. The optical band gap of BaTiO3 is found to be 3.72 eV and 2.22 eV for CdSe QDs. The CdSe QDs sensitized BaTiO3 heterostructure's photo-electrochemical water splitting behaviour is examined in 1 M Na2 S electrolyte under 100 mW/cm 2 light illumination. As photoanode, CdSe QDs sensitized BaTiO3 heterostructure demonstrated ∼ 32.5 mA/cm 2 under illumination and ∼ 25 mA/cm 2 in dark at 0.8 V. (vs. Ag/AgCl), which implies that photocurrent density of 12 mA/cm 2 at 0.8 V. (vs. Ag/AgCl). This work discusses the significance and novelty of the usage of CdSe QDs sensitized BaTiO3 heterostructure as photo-electrocatalyst and paves pathway for newer materials development for enhanced photo-electrochemical water splitting.